POLA KOMUNIKASI POLITIK CALON PRESIDEN PADA PEMILIHAN PRESIDEN-WAKIL PRESIDEN TAHUN 2019 - ARTHA MEDITA; NURAINY HANIFAH (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Communication in political marketing plays an important role in political mobilization, building trust both in political actors and the government. Using a phenomenological approach, a total of 19 in depth interviews with voters were conducted to gain rich insight into perceptions of the complexity of political symbolism, and trust among voters. This study conceptualized political communication as a dual approach. The political brand promise is intrinsically linked to cultural references and conveyed through symbolic communication combined with a distinctive brand message. This builds trust, which then affects political participation.